Lipid extraction by boron nitride nanosheets from liquid-ordered and liquid-disordered nanodomains. Issue 29 (12th July 2018) - Zhang, Yonghui; Chan, Chun; Li, Zhen; Ma, Jiale; Meng, Qiangqiang; Cheng, Xiaolin; Fan, Jun
Abstract : Atomically thin boron nitride nanosheets are important two-dimensional nanomaterials with great potential in biomedical applications. Abstract : Atomically thin boron nitride nanosheets are important two-dimensional nanomaterials with great potential in biomedical applications. Understanding the basic interaction mechanisms between lipid domains and boron nitride nanosheets can help clarify the potential risks of these nanomaterials and thus provide guidance on the design of safe biomedical applications. Using molecular dynamics simulations, we demonstrate that the BNNS can disrupt the liquid disordered lipid bilayers much more easily compared to the liquid ordered phases. The potential of mean force profiles calculated from umbrella sampling further explain this adsorption preference. When the BNNS is placed at the boundary of the liquid ordered and liquid disordered nanodomains, disruption of the liquid ordered domains becomes much easier due to the presence of adjacent liquid disordered domains. Our findings provide new insights into the cytotoxicity of boron nitride nanosheets interacting with cellular membranes.